Sensorimotor Processing in the Newborn Rat Red Nucleus during Active Sleep - Del Rio-Bermudez, Carlos (J Neurosci, 2015)
Sensory feedback from sleep-related myoclonic twitches is thought to drive activity-dependent development in spinal cord and brain. However, little is known about the neural pathways involved in the generation of twitches early in development. The red nucleus (RN), source of the rubrospinal tract, has been implicated in the production of phasic motor activity during active sleep in adults. Here we hypothesized that the RN is also a major source of motor output for twitching in early infancy, a period when twitching is an especially abundant motor behavior. We recorded extracellular neural activity in the RN during sleep and wakefulness in 1-week-old unanesthetized rats. Neurons in the RN fired phasically before twitching and wake movements of the contralateral forelimb. A subpopulation of neurons in the RN exhibited a significant peak of activity after forelimb movement onset, suggesting reafferent sensory processing. Consistent with this observation, manual stimulation of the forelimb evoked RN responses. Unilateral inactivation of the RN using a mixture comprising GABA(A), GABA(B), and glycine receptor agonists caused an immediate and temporary increase in motor activity followed by a marked and prolonged decrease in twitching and wake movements. Altogether, these data support a causal role for the RN in infant motor behavior. Furthermore, they indicate that twitching, which is characterized by discrete motor output and reafferent input, provides an opportunity for sensorimotor integration and activity-dependent development of topography within the newborn RN.